Peningkatan Visibilitas Online UMKM Alfiancake melalui Sosialisasi Digital Marketing dan Pelatihan Desain Konten Visual Website - Devan Pratama Kwan; Vina Safitri; Alex Kisanjani; Marulan Andivas; Nana Sugiono (Dedikasi: Jurnal Pengabdian Pendidikan dan Teknologi Masyarakat, 2026)
Digital transformation requires Micro, Small, and Medium Enterprises (MSMEs) to adapt in order to sustain their existence. "Alfiancake", an MSME located in Teritip Village, East Balikpapan, operates an independent promotional website, yet its online visibility remains suboptimal due to limited digital marketing literacy and simple product visuals with plain backgrounds. This community service project aims to enhance the partner’s digital capacity and competitiveness through two main approaches: digital marketing strategy socialization and promotional visual content design training. The method applied was a participatory approach consisting of problem mapping, planning, implementation, as well as monitoring and evaluation. Through this program, the management of Alfiancake was educated on separating business accounts and trained to utilize the Canva application to edit existing product photo backgrounds into more aesthetic visuals, while embedding crucial information such as product names, variants, and product advantages. The results demonstrated a significant improvement in the owner's digital skills, with the partner's promotional website now updated with more informative, professional, and representative visual content to serve as a digital storefront for reaching a broader market.